Clinical, biochemical, and molecular overview of transaldolase deficiency and evaluation of the endocrine function: Update of 34 patients. Issue 1 (11th February 2019) - Williams, Monique; Valayannopoulos, Vassili; Altassan, Ruqaiah; Chung, Wendy K.; Heijboer, Annemieke C.; Keng, Wei Teik; Lapatto, Risto; McClean, Patricia; Mulder, Margot F.; Tylki‐Szymańska, Anna; Walenkamp, Marie‐Jose E.; Alfadhel, Majid; et al.
Abstract: Background: Transaldolase deficiency (TALDO‐D) is a rare autosomal recessive inborn error of the pentose phosphate pathway. Since its first description in 2001, several case reports have been published, but there has been no comprehensive overview of phenotype, genotype, and phenotype–genotype correlation. Methods: We performed a retrospective questionnaire and literature study of clinical, biochemical, and molecular data of 34 patients from 25 families with proven TALDO‐D. In some patients, endocrine abnormalities have been found. To further evaluate these abnormalities, we performed biochemical investigations on blood of 14 patients. Results and conclusions: Most patients ( n = 22) had an early‐onset presentation (prenatally or before 1 month of age); 12 patients had a late‐onset presentation (3 months to 9 years). Main presenting symptoms were intrauterine growth restriction, dysmorphic facial features, congenital heart disease, anemia, thrombocytopenia, and hepato(spleno)megaly. An older sib of two affected patients was asymptomatic until the age of 9 years, and only after molecular diagnosis was hepatomegaly noted. In some patients, there was gonadal dysfunction with low levels of testosterone and secondary luteinizing hormone (LH) and follicle‐stimulating hormone (FSH) abnormalities later in life. This overview provides information that can be helpful for managing patients and counseling families regarding prognosis. Diagnostic guidelines, possible genotype–phenotype correlations, treatment options, and pathophysiological disease mechanisms are proposed.